Impact of radiation on the MHD couple stress hybrid nanofluid flow over a porous sheet with viscous dissipation - Mahesh, R.; Mahabaleshwar, U. S.; Kumar, P. N. Vinay; Öztop, Hakan Fehmi; Abu-Hamdeh, Nidal (Elsevier, 2023)
The investigation is carried to observe the impact of radiation on the MHD couple stress hybrid nanofluid over porous sheet with dissipation. The water based MHD couple stress hybrid nanofluid flow due to porous shrinking sheet with thermal radiation and viscous dissipation has range of engineering applications dealing with energy distribution, solar energy storage, chemical reactors and polymer production. The flow problem is mathemati-cally modelled into nonlinear partial differential equations, which are transformed into set of ordinary differ-ential equations via similarity variable. The analytical solutions are derived in the form of hypergeometric functions. These results are in line with the existing classical results. The physical insights on the impact of MHD, mass transpiration, Eckert number, Couple stress, porosity and thermal radiation on velocity and temperature profiles are provided by means of graphs.
Keywords: MHD; Couple stress; Thermal radiation; Viscous dissipation; Eckert number; Porous medium